PENGARUH KEPEMIMPINAN SINERGIS DAN KECERDASAN EMOSIONAL TERHADAP ETOS KERJA PEREMPUAN KOMUNITAS SADAYA JAKARTA - Anandha Budiantoro; Saepudin Saepudin (Media Bina Ilmiah, 2023)
This study aims to determine and analyze the effect of synergistic leadership and emotional quotion on the work ethic of the Sadaya Community at Jakarta. This research uses quantitative research methods with survey techniques to answer the hypothesis test that has been formulated. Respondents amounted to 200 people, the sampling technique used was random sampling technique. The synergistic leadership, emotional quotion and work ethic questionnaires were validated by the product moment correlation formula, reliability was measured by the Cronbach's Alpha formula. Hypothesis testing using the PLS SEM analysis application. The results of the study show that synergistic leadership has a direct and significant effect on work ethic, emotional quotion has a direct positive and significant effect on work ethic. Synergy leadership has a direct and significant influence on Emotional quotion. So that in an effort to improve the work ethic can be done through increasing the effectiveness of synergistic leadership and emotional quotion. From the results of the study it was concluded that synergistic leadership has a direct and significant effect on work ethic, emotional quotion has a direct positive and significant effect on work ethic, and synergistic leadership has a direct and significant effect on emotional quotion